2019
DOI: 10.3390/genes10080572
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Pathway Genetic Variation and Thyroid Cancer

Abstract: Vitamin D is mostly known for its role in bone and calcium metabolism. However, studies have suggested that it also has inhibitory effects on tumor development and progression. Genetic variants close to genes that encode crucial enzymes for the synthesis (DHCR7 rs12785878), metabolism (CYP2R1 rs2060793) and degradation (CYP24A1 rs6013897) of vitamin D have been associated with serum levels of vitamin D. The aim of this case-control study was to determine the effect of these variants in the vitamin D pathway on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Venous blood samples were collected from each subject, and genomic deoxyribonucleic acid (DNA) was extracted from peripheral blood leucocytes using previously described methods [ 12 ]. Genotyping of the rs12785878, rs2060793 and rs6013897 SNPs was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using previously described methods and custom-designed primers [ 13 ]. For each of these SNPs, 100 ng of genomic DNA was used in 15 μL reactions containing 0.25 μM of each primer, 1 U of Taq DNA polymerase and respective buffer (DreamTaq Green DNA polymerase, Thermo Fisher Scientific, Waltham, MA, USA) and 200 μM of each deoxynucleotide (dNTP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous blood samples were collected from each subject, and genomic deoxyribonucleic acid (DNA) was extracted from peripheral blood leucocytes using previously described methods [ 12 ]. Genotyping of the rs12785878, rs2060793 and rs6013897 SNPs was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using previously described methods and custom-designed primers [ 13 ]. For each of these SNPs, 100 ng of genomic DNA was used in 15 μL reactions containing 0.25 μM of each primer, 1 U of Taq DNA polymerase and respective buffer (DreamTaq Green DNA polymerase, Thermo Fisher Scientific, Waltham, MA, USA) and 200 μM of each deoxynucleotide (dNTP).…”
Section: Methodsmentioning
confidence: 99%
“…Amplified fragments were then digested with the appropriate restriction enzyme (New England Biolabs, Beverly, MA, USA or Thermo Fisher Scientific, Waltham, MA, USA), according to the manufacturer’s instructions, and visualized after electrophoresis on a 2% or 3% agarose gel. The identification of the rs12785878, rs2060793 and rs6013897 SNPs was based on the different fragments produced after digestion with the TaqI, SchI and TscAI restriction enzymes, respectively [ 13 ]. Genotyping of the GC rs2282679 SNP was performed by a TaqMan SNP genotyping assay with a commercially available TaqMan probe (Assay ID: C-26407519-10; Thermo Fisher Scientific, Waltham, MA, USA), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, compelling evidence reveals the roles of vitamin D on extraskeletal diseases, such as infectious disease [2], cardiovascular disease [3], autoimmune disease [4], neurodegeneration [5], and cancer [6]. Deficiency of vitamin D has been reported to be relevant to oral squamous cell carcinoma [7], breast cancer [8], colorectal cancer [9], prostate cancer [10], pancreas cancer [11], thyroid cancer [12], hepatocellular carcinoma [13], and ovarian cancer [14]. Furthermore, vitamin D supplementation may decrease the death of cancer by 16% [15].…”
Section: Introductionmentioning
confidence: 99%
“…There has an individual variability in serum vitamin D stores which cannot be explained alone by age, sunlight exposure, body mass index, or dietary intake [12]. Studies have demonstrated that vitamin D level is highly heritable [16].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of 1,25-(OH) 2 D 3 to its receptor results in pleiotropic effects regulating calcium-phosphate metabolism, cell proliferation, differentiation, apoptosis, angiogenesis and metastasis. Vitamin D can thus be described as a very important agent in the anti-cancer response [3]. Accordingly, many studies have shown the anticancer effects of vitamin D on breast, prostate, colon and endocrine cancers [20].…”
Section: Abstract Medullary Thyroid Carcinoma Vitamin D Vitamin D Receptor Polymorphism Introductionmentioning
confidence: 99%